Theorizing Program Quality in Web-Based Adult Education - Pamela Ann Harroff; Thomas Valentine (Adult Education Research Conference, 2004)
The purpose of the study was to discover dimensions of quality in web based adult education and to map those dimensions in a wide range of programs. The focus of the study was to develop a typology of the types of programs with respect to the quality dimensions of web-based adult education. Cluster analysis was used to develop a typology of web-based adult education.